2020
DOI: 10.36877/jhis.a0000092
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intention to Purchase Halal Cosmetic Products: A Study on Muslim Women in West Malaysia

Abstract: The demand on global halal cosmetics market is anticipated to reach USD 53 billion by the end of 2023. In fact, the rising awareness about percutaneous essence of conventional cosmetic products has made consumers shift to “halal” cosmetics. Malaysia is one of the country in providing full support to promote “halal” certification process on halal cosmetic products. Products certified “halal” by JAKIM are Halal products as it is safe to consume, nutritious and also the products are quality controlled. In accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…According to the result, it showed that Malaysia had the highest rank in the research of halal cosmetics. Referring to Wei et al (2020), Malaysia was one of the earliest countries that had awareness and moved forward to halal cosmetics. Despite this, Malaysia had developed some synchronized strategies to enhance the halal cosmetic industry such as established Halal Industry Development Corporation (HDC) to assist in developing strategies and expanding more market on the halal industry.…”
Section: Studies Included In Review (N=34)mentioning
confidence: 99%
“…According to the result, it showed that Malaysia had the highest rank in the research of halal cosmetics. Referring to Wei et al (2020), Malaysia was one of the earliest countries that had awareness and moved forward to halal cosmetics. Despite this, Malaysia had developed some synchronized strategies to enhance the halal cosmetic industry such as established Halal Industry Development Corporation (HDC) to assist in developing strategies and expanding more market on the halal industry.…”
Section: Studies Included In Review (N=34)mentioning
confidence: 99%
“…Sertifikasi pada produk kosmetik halal juga menjadi peranan penting bagi produsen di Malaysia. Konsumen akan lebih percaya menggunakan suatu kosmetik halal, jika produk tersebut telah memiliki sertifikat dari badan resmi Malaysia seperti JAKIM (WEI et al, 2020). Milenial di Malaysia bersikap proaktif pada produk kosmetik.…”
Section: Gambar 4 Penjualan Kosmetik Melalui E-commerceunclassified
“…Furthermore, given the limited understanding in this area, the current study examines the role of religiosity as a moderator and that of trust in the form of a mediator (Wei, Mohamad & Kuah, 2020) between attitude toward using online and purchase intention through online platform system in halal cosmetic. Thus, the extended original TAM is accumulating trust and religiosity as other variables that affect consumer purchase intention online in halal cosmetics and is more comprehensive compared with previous studies.…”
Section: Introductionmentioning
confidence: 99%